Adobe Acrobat: an alternative electronic teaching file construction methodology independent of HTML restrictions. - Katzman GL (Journal of Digital Imaging, 2002)
The goal of the project was to create a method by which an in-house digital teaching file could be constructed that was simple, inexpensive, independent of hypertext markup language (HTML) restrictions, and appears identical on multiple platforms. To accomplish this, Microsoft PowerPoint and Adobe Acrobat were used in succession to assemble digital teaching files in the Acrobat portable document file format. They were then verified to appear identically on computers running Windows, Macintosh Operating Systems (OS), and the Silicon Graphics Unix-based OS as either a free-standing file using Acrobat Reader software or from within a browser window using the Acrobat browser plug-in. This latter display method yields a file viewed through a browser window, yet remains independent of underlying HTML restrictions, which may confer an advantage over simple HTML teaching file construction. Thus, a hybrid of HTML-distributed Adobe Acrobat generated WWW documents may be a viable alternative for digital teaching file construction and distribution. Copyright © 2001 by W.B. Saunders Company